Permanent monitoring of native forests in the protected areas of Chile: an urgent need - Salas-Eljatib, Christian; Vargas-Gaete, Rodrigo; Soto, Daniel P; Donoso, Pablo J (BOSQUE, 2023)
Forest dynamics describe the change in structure and composition of forests over time, and is mainly driven by forest growth, a process resulting from size increase and mortality of trees, and recruitment of new individuals. An understanding of forest growth is essential for decision-making and research. An appropriate characterization of growth is only possible through the remeasurement of permanent sample plots over time. Although Chile has a continuous forest inventory system, it has several deficiencies which prevent the effective study of forest growth, mainly because it focuses on stand-level variables and stock estimates but lacks data for individual trees. Furthermore, access to the raw data is limited. In addition, maintaining long-term monitoring of plots to evaluate growth is difficult because of budget restrictions. These combined factors jeopardize the provision of key information regarding native forest dynamics and growth. We propose the establishment of a network of permanent sample plots in the Chilean National System of Protected Areas. Finally, we discuss a monitoring system based on this network by highlighting the advantages in terms of research, dissemination, outreach, and the ease of adding non-woody attributes.